Role of Antioxidants in Assisted Reproductive Techniques - Agarwal, Ashok (World J Mens Health, 2017)
Oxidative stress (OS) has been recognized as a significant cause of suboptimal assisted reproductive outcome. Many of the sperm preparation and manipulation procedures that are necessary in the in vitro environment can result in excessive production of reactive oxygen species (ROS) thereby exposing the gametes and growing embryos to significant oxidative damage. Antioxidants have long been utilized in the management of male subfertility as they can counterbalance the elevated levels of ROS inducing a high state of OS. Few studies have looked into the clinical effectiveness of antioxidants in patients undergoing assisted reproduction. While an overall favorable outcome has been perceived, the specific clinical indication and optimal antioxidant regimen remain unknown. The goal of our review is to explore the sources of ROS in the in vitro environment and provide a clinical scenario-based approach to identify the circumstances where antioxidant supplementation is most beneficial to enhance the outcome of assisted reproduction.